Comparing environmental civil society in Singapore and the Philippines - Teoh, Terese Anne Hui Shan (Nanyang Technological University, 2024)
The aim of this research is to understand the differences in environmental activism in Singapore and the Philippines and to account for those differences. In-depth and semi-structured interviews were conducted with environmental activists, 7 from Singapore and 5 from the Philippines. Activists interviewed identified as male, female, and queer. Second, content analysis was carried out to analyse the social media posts, press releases and media statements made by different environmental activist groups in both countries. I apply the three dominant theoretical approaches in social movement theory: political opportunity structures, resource mobilisation theory and framing theory, which correspond to the macro-level, meso-level and micro-level of analyses respectively. I then investigate which theory has the most explanatory power and possible influence on the other two phenomena. By analysing how different political institutions influence different political cultures and organisational resources, I uncover why a particular movement-sponsored issue gains traction in one country but not another, or why a movement frame takes off in one place but not another. Through this study, I argue that environmental civil society is largely determined by political opportunity structures within countries, due to the creation of path-dependent structures that create top-down and bottom-up influences on the movement.